Service quality gaps and their role in service enterprises development - Urban, Wiesław (Technological and Economic Development of Economy, 2009)
The study takes into consideration the problem of organizational quality gaps where the quality losses occur. Many service quality gaps are reviewed in this paper. But the four out of five quality gaps by Parasuraman et al.(1985) are examined. The main management problem, according to research achievements, is the gap between managers’ perception of customers’ expectation and service specifications existing in organizations. In a service organization usually more quality gaps might be identified. Identification of specific quality gaps is advantageous from a management point of view. Paslaugų kokybės problemos ir jų vaidmuo paslaugų teikimo įmonių plėtrai Santrauka. Straipsnyje nagrinėjamos organizacinės kokybės problemos. Čia apžvelgiama daugelis paslaugų kokybės problemų, bet tiriamos tik keturios iš penkių (pagal Parasuraman et al. 1985). Tyrimų duomenys rodo, jog pagrindinė problema yra skirtumas tarp to, kaip klientų lūkesčius supranta vadybininkai ir kaip organizacijoje yra apibūdinamos paslaugos. Taigi daugiausia kokybės problemų kyla planuojant paslaugas. Vadybiniu požiūriu yra labai naudinga nustatyti kokybės problemas. Reikšminiai žodžiai: paslaugų valdymas, paslaugų kokybė, paslaugų kokybės problemos. First published online: 21 Oct 2010